A Review of the Managerial Practices of Guidance and Counseling Services in Supporting Students’ Learning Autonomy in Junior High Schools under the Merdeka Curriculum (A Study at Public Junior High Schools in Bireuen Regency) - Syarifah Wahidah; Neviyarni; Firman (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study aims to examine the managerial practices of Guidance and Counseling services in supporting students' learning autonomy within the implementation of the Merdeka Curriculum. The Merdeka Curriculum emphasizes the holistic development of students’ competencies, including self-directed learning as a key component of the Pancasila Student Profile. In this context, guidance and counseling services play a strategic role, particularly in assisting students in identifying their potential, designing learning goals, and managing time and learning strategies independently. This research employed a qualitative case study approach, with data collected through interviews, observations, and document analysis involving counseling guidance teachers and students at a junior high school. The results reveal that well-planned, organized, and continuously evaluated Guidance and Counseling services contribute positively to students’ learning autonomy. However, challenges such as limited-service time and lack of managerial training for counseling guidance teachers remain. The findings recommend strengthening the managerial capacity of counseling guidance teachers to optimize service delivery in alignment with the goals of the Merdeka Curriculum.